It's All in How You Think About It: Construal Level and the Iowa Gambling Task - Okdie, Bradley M.; Buelow, Melissa T.; Bevelhymer-Rangel, Kurstie (Frontiers in Neuroscience, 2016)
Recent research has identified a number of factors that can influence performance on the Iowa Gambling Task (IGT) when it is used in clinical or research settings. The current studies examine the effects of construal level theory (CLT) on the IGT. Study 1 suggests that when primed with a high construal mindset (i.e., thinking abstractly versus concretely), individuals learned to avoid Deck A more than those primed with a low construal mindset. Study 2 suggests that when construal level is manipulated through psychological distance (i.e., selecting for a close versus distant friend), individuals in a high construal mindset instead showed a preference for Deck A compared to individuals in a low construal mindset or a control group. Taken together, these studies suggest that IGT performance is impacted by the manner in which one construes the task. Implications for decision making research and use of the IGT as a clinical and research instrument are discussed.